(untitled) (Journal of Pharma Insights and Research, 2025)
Implantable drug delivery systems (IDDS) provide precise and sustained medication release at targeted anatomical sites. These systems overcome traditional drug delivery limitations through sophisticated mechanisms including diffusion-controlled release, osmotic pressure gradients, and biodegradable polymer matrices. The evolution of IDDS includes passive polymeric implants, both biodegradable and non-biodegradable, as well as active systems like mechanical and osmotic pumps. Modern manufacturing techniques such as hot melt extrusion, compression molding, and emerging 3D printing technologies have enhanced the precision and scalability of IDDS production. While these systems offer numerous advantages including improved bioavailability, reduced dosing frequency, and targeted therapeutic action, challenges persist regarding surgical implementation, biocompatibility, and reversibility. Clinical applications span multiple therapeutic areas, with notable success in contraception, cancer therapy, and chronic pain management. Recent developments in smart materials and microelectronics have led to more sophisticated systems capable of responsive drug release. The continuous advancement in polymer science, manufacturing technologies, and understanding of biological interfaces suggests expanding applications for IDDS in personalized medicine and chronic disease management